Therapeutic outdoor design for mental patients / Abd. Haris Shamsuddin - Shamsuddin, Abd. Haris (2004)
The awareness that outdoor design may promote health was discovered during the earliest Civilization of man. Gardens were known as places that could provide peacefulness and rest, as Well as to offer therapeutic benefit. However, as the interest in science advanced, the role of Outdoor design for therapeutic purposes has been neglected. Studies have indicated that there Are four considerations in designing an outdoor area that may contribute therapeutic benefits: I) it should promote a sense of control amongst patients as well as to allow privacy; Ii) the arrangement should accommodate social support from visitors, relatives and Administration staff; Hi) the layout should encourage physical movement for users as well as exercise activities; Iv) it should provide access to nature as well as other positive distractions. In general, mental patients are physically fit. However, they are in a position of mental disorder and the curing treatment concentrates on evoking their memory and rationalising their thinking Ability. Therefore, it is suggested that the focus of outdoor therapeutic design for mental patients should be aimed towards reducing their stress as well as stimulating the mind gradually